New guidelines for the treatment of seasonal allergic rhinitis - Emeryk, Andrzej; Emeryk-Maksymiuk, Justyna; Janeczek, Kamil (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2019)
The paper discusses the classification and forms of allergic rhinitis with a special focus on seasonal allergic rhinitis (SAR). The general principles of SAR management are presented, including the role of nasal glucocorticoids, nasal and oral antihistamines, and antileukotrienes. Based on the latest guidelines, the current rules for the selection of drugs in the therapy of SAR are given, paying special attention to the initial treatment. The aim of the paper is to present updated guidelines for the pharmacological management of patients with seasonal allergic rhinitis.